Pengaruh Penerapan Model Take And Give Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 1 Pagaran Kabupaten Tapanuli Utara Tahun Pelajaran 2023/2024 - Martha Ferisay Hutasoit; Oktober Tua Aritong; Ronny Simatupang; Betty A.S. Pakpahan; Sandy Ariawan (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The purpose of this research is to determine the positive and significant influence of the Take And Give model on the learning activity of Christian Religious Education for Class VIII Students at SMP Negeri 1 Pagaran for the 2023/2024 Academic Year. The method used in this research is quantitative descriptive research type pre experimental design in the form of a one shot case study. The population is all class VIII students of SMP N 1 Pagaran for the 2023/2024 academic year, totaling 159 students and 32 students were determined as the sample selected using a purposive sampling technique. Data was collected using observation sheets and a 34 item questionnaire. 17 items for the observation sheet for variable Thus it is known that there is a positive relationship between variables and Y. Test the regression equation, obtained the regression equation Y ̂="30.16"+0.48X. Regression coefficient of determination test r2 = 25.2%. Testing the hypothesis using the F test obtained Fcount > Ftable = (α=0.05, dk numerator k =15, dk denominator = n-2=32-2=30) namely 10.24 > 2.01. Thus, Ha is accepted, Ho is rejected.